Relationship between pregnancy complications and subsequent coronary artery disease assessed by coronary computed tomographic angiography in black women - Wichmann, Julian; Takx, Richard A. P.; Nunez, Johanna H.; Vliegenthart, Rozemarijn; Otani, Katharina; Litwin, Sheldon E.; Morris, Pamela B.; De Cecco, Carlo N.; Rosenberg, Russell D.; Bayer, Richard R.; Baumann, Stefan; Renker, Matthias; et al. (Circulation. Cardiovascular imaging, 2019)
Background:Maternal pregnancy complications, particularly preeclampsia and gestational diabetes mellitus, are described to increase the risk for subsequent coronary artery disease (CAD). In addition, black women are at higher risk for CAD. The objective of this study was to compare the prevalence and extent of CAD as detected by coronary computed tomographic angiography (CCTA) in black women with and without a history of prior pregnancy complications.Methods:We retrospectively evaluated patient characteristics and CCTA findings in groups of black women with a prior history of preterm delivery (n=154), preeclampsia (n=137), or gestational diabetes mellitus (n=148), and a matched control group of black women who gave birth without such complications (n=445). Univariate and multivariate analyses were performed to assess risk factors of CAD.Results:All groups with prior pregnancy complications showed higher rates of any (≥20% luminal narrowing) and obstructive (≥50% luminal narrowing) CAD (preterm delivery: 29.2% and 9.1%; preeclampsia: 29.2% and 7.3%; and gestational diabetes mellitus: 47.3% and 15.5%) compared with control women (23.8% and 5.4%). After accounting for confounding factors at multivariate analysis, gestational diabetes mellitus remained a strong risk factor of any (odds ratio, 3.26; 95% CI, 2.03-5.22; P<0.001) and obstructive CAD (odds ratio, 3.00; 95% CI, 1.55-5.80; P<0.001) on CCTA.Conclusions:Black women with a history of pregnancy complications, particularly gestational diabetes mellitus, have a higher prevalence of CAD on CCTA while only a history of gestational diabetes mellitus was independently associated with any and obstructive CAD on CCTA.